Isolation and characterization of nine polymorphic microsatellite loci in Piper solmsianum (piperaceae)1. (4th April 2014) - Yoshida, Nídia C.; Lima, Paula F.; Priolli, Regina H. G.; Kato, Massuo J.; Colombo, Carlos A.
Abstract : Premise of the study: Nine microsatellite (simple sequence repeat [SSR]) loci were characterized for natural populations of Piper solmsianum, a potential source of bioactive secondary metabolites, and analyzed to assess the levels of genetic diversity in this species. Methods and Results: Based on an enriched library using the oligonucleotides (CT)8 and (GT)8, a total of 19 pairs of SSR primers were designed and nine of them were highly polymorphic after screening of 37 specimens from two populations. The number of alleles per locus ranged from one to six while the observed heterozygosity for polymorphic loci ranged from 0.000 to 0.875. Conclusions: The SSR regions characterized were informative, and the genetic markers will be useful to assess the genetic diversity and gene flow in populations of P. solmsianum .